The Effects of Task Complexity and Input Frequency on the Acquisition of the Past Counterfactual Construction Through Recasts. Issue 3 (23rd July 2014) - Révész, Andrea; Sachs, Rebecca; Hama, Mika
<x xml:space="preserve">Abstract</x> This investigation examined two techniques that may help learners focus on second language (L2) constructions when recasts are provided during meaning‐based communicative activities: altering the cognitive complexity of tasks and manipulating the input frequency distributions of target constructions. We first independently assessed the validity of our cognitive task complexity manipulation by means of expert judgments, dual‐task methodology, and eye tracking. Next, in our main study, we employed a pretest‐posttest design with two treatment sessions. The participants were 51 adult English L2 learners, randomly assigned to one of four experimental groups or a control group. All experimental groups received recasts but differed as to whether they carried out simple tasks with lower reasoning demands or complex tasks with higher reasoning demands, and whether they received skewed or balanced input of the linguistic target, the past counterfactual construction. An oral production test and two written receptive tests were utilized to measure changes in participants' knowledge. Our results revealed no effects for the input frequency manipulations, but participants achieved higher oral production gains under the simple task condition.